Camp Rock: Hidden Tracks - Perelman, Helen (Disney Enterprises Inc, 2008)
When Brown announces a scavenger hunt, the campers go wild. But they get even more pumped when he announces that the winner will get a hidden track on Connect Three's new album! Mitchie and Caitlyn team up to be winners, but some news from Lola throws them off their game.
Keywords: Camping & Outdoor Activities; Juvenile Fiction; Sports & Recreation